Polyethylene naphthalate as well as preparation method and application thereof

By introducing more rigid aromatic ring structures in polyethylene naphthalate and adopting segmented precise temperature and pressure control technology, the existing PEN-based flexible printed circuit boards have been solved in the heat resistance, mechanical properties and flame retardant properties of existing PEN-based flexible printed circuit boards. The shortcomings in the aspects have achieved significant improvements in material performance and met the demand for high-performance flexible printed circuit boards in automotive electronic control systems.

CN119431753AInactive Publication Date: 2025-02-14SHANDONG IND RES ZHONGKE HIGH END CHEM IND TECH RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510031036.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polyethylene naphthalate (PEN)-based flexible printed circuit boards have many problems in raw material processing, formula design and preparation processes, including insufficient flame retardant performance, difficult to balance material toughness and rigidity, and uneven product performance , large fluctuations, unstable size and weak surface adhesion, making it difficult to meet the demand for high-performance flexible printed circuit boards in automotive electronic control systems.

Method used

By adding polybasic acid or anhydride such as phenylatic acid dianhydride, 1,4,5,8-naphthalene tetracarboxylic acid dianhydride and copolymerizing with the main raw materials, more rigid aromatic ring structures are introduced, and the regularity of the molecular chain is enhanced to enhance the material heat resistance. At the same time, a process of precise temperature and pressure control is adopted in segments to protect nitrogen from oxidation and improve material performance.

Benefits of technology

It significantly improves the heat resistance, mechanical properties and flame retardant properties of the material, can adapt to the complex and high-temperature working environment of the automotive electronic control system, ensures the stable operation of the product under high temperature conditions, and improves the overall performance of the material, meeting industrial production need.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of polyethylene naphthalate production, in particular to polyethylene naphthalate as well as a preparation method and application thereof. The preparation method of the polyethylene naphthalate comprises the following steps: putting the raw materials into a reaction kettle, heating and raising the temperature, and carrying out transesterification; after the ester exchange reaction is completed, raising the temperature to 260-280 DEG C, reducing the pressure of a reaction system to 10-100 Pa, and carrying out condensation polymerization reaction for 1-3 hours; and after the condensation polymerization reaction is finished, stopping heating, discharging the product from the reaction kettle, and carrying out grain-sized dicing treatment to obtain granular polyethylene naphthalate. By adding polybasic acids or acid anhydrides such as pyromellitic dianhydride and 1, 4, 5, 8-naphthalene tetracarboxylic dianhydride to be copolymerized with the main raw materials, more rigid aromatic ring structures are introduced, the regularity of molecular chains is enhanced, the heat resistance of the material is greatly improved, and the material can adapt to a complex and high-temperature working environment of an automobile electronic control system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyethylene naphthalate production, in particular to polyethylene naphthalate and a preparation method and application thereof. Background Art

[0002] Polyethylene naphthalate (PEN)-based materials have a unique chemical structure and show higher heat resistance, mechanical strength and chemical stability than traditional polyester materials, making them a very promising candidate material for the preparation of high-performance flexible printed circuit boards. The naphthalene ring structure in its molecules gives the material excellent thermal properties, allowing PEN to maintain good dimensional stability and mechanical properties in high-temperature environments, and can meet the connection requirements of electronic components in high-temperature areas such as automobile engine compartments. However, at this stage, there are many problems that need to be solved in the use of PEN to prepare flexible printed circuit boards suitable for automotive electronic control systems.

[0003] In the raw material processing link, traditional processes often ignore the fine pretreatment of PEN resin and related raw materials. In raw material processing, the moisture and impurities of PEN resin are not completely removed, and the surface modification of inorganic fillers is not good, which affects the subsequent processing and material performance. From the perspective of material formulation, the existing PEN-based flexible printed circuit board formulation design is not perfect. On the one hand, the flame retardant performance is insufficient. Once a short circuit or other fault occurs in the automotive electronic system and causes a fire, if the flexible printed circuit board does not have efficient flame retardant properties, the fire will spread rapidly, posing a huge threat to the safety of the entire car. The amount of flame retardant added in the traditional formula is unreasonable or the flame retardant system is single, which cannot form an effective heat insulation, oxygen isolation and flame retardant barrier, and it is difficult to meet the increasingly stringent fire safety standards of the automotive industry. On the other hand, it is difficult to balance the toughness and rigidity of the material. While pursuing high rigidity to ensure the dimensional accuracy of the circuit board and carry electronic components, the toughness of the material is often sacrificed, causing the circuit board to crack and break easily when bent, installed or slightly impacted, affecting its service life and reliability. In terms of preparation process, the mixing is rough, and the single-screw or simple stirring equipment cannot fully and evenly mix the raw materials, resulting in uneven and fluctuating product performance. The heat setting and surface modification treatments after molding are not fine, the dimensions are unstable, and the surface adhesion is weak, affecting the function and reliability of FPC.

[0004] In summary, the existing PEN-based flexible printed circuit board preparation technology has a series of problems in raw material processing, formula design and preparation process. A comprehensive optimization and fine-tuned preparation scheme is urgently needed to meet the urgent demand of automotive electronic control systems for high-performance flexible printed circuit boards. Summary of the invention

[0005] In view of the above deficiencies in the prior art, the object of the present invention is to provide a polyethylene naphthalate, which is copolymerized with the main raw material by adding a polyacid or anhydride such as pyromellitic dianhydride and 1,4,5,8-naphthalenetetracarboxylic dianhydride, thereby introducing more rigid aromatic ring structures, enhancing the regularity of the molecular chain, and greatly improving the heat resistance of the material, so that it can adapt to the complex and high-temperature working environment of automotive electronic control systems.

[0006] Another object of the present invention is to provide a method for preparing polyethylene naphthalate, which effectively improves the performance of the material and meets the needs of high-end fields through segmented precise temperature and pressure control and nitrogen protection and anti-oxidation.

[0007] The third object of the present invention is to provide an application of polyethylene naphthalate for the preparation of flexible printed circuit boards for automotive electronic control systems. The prepared product has excellent performance and is particularly suitable for flexible printed circuit boards for automotive engine control units, in-vehicle entertainment systems, and airbag control systems.

[0008] The present invention is achieved by adopting the following technical solutions: The preparation method of polyethylene naphthalate comprises the following steps: (1) Adding 100 parts of 2,6-naphthalene dicarboxylic acid dimethyl ester containing a modified component, 60-75 parts of ethylene glycol, 10-30 parts of terephthalic acid, 5-20 parts of pyromellitic anhydride, 5-20 parts of 1,4,5,8-naphthalene tetracarboxylic anhydride, 5-15 parts of cardanol, 0.05-1 parts of an organic nucleating agent, 1-5 parts of a composite heat stabilizer, 8-20 parts of a halogen flame retardant, 0.1-1 parts of an antioxidant, 0.5-3 parts of an antistatic agent and a composite catalyst solution into a reactor for ester exchange reaction, wherein the amount of the composite catalyst solution is determined by 0.05%-0.5% of the mass of 2,6-naphthalene dicarboxylic acid dimethyl ester containing a modified component; heating and heating, the stirring speed is controlled at 50-200 rpm, the reaction temperature is controlled at 180-220° C., and the reaction time is 2-6 hours; the stirring speed is preferably 120-150 rpm; (2) After the transesterification reaction is completed, the temperature is raised to 260-280°C, and the pressure of the reaction system is reduced to 10-100 Pa to carry out polycondensation reaction for 1-3 hours; (3) After the polycondensation reaction is completed, the heating is stopped and the mixture is cooled naturally under the protection of nitrogen. When the temperature drops to 100-150°C, the product is discharged from the reactor and pelletized to obtain polyethylene naphthalate.

[0009] The preparation method of dimethyl 2,6-naphthalene dicarboxylate containing a modified component comprises the following steps: a. Add the nano-silica suspension to the reactor, then add 100 parts by mass of naphthalene, 200 parts by mass of methanol, 5 parts by mass of pyromellitic anhydride, 10 parts by mass of dimethyl adipate and 0.5 parts by mass of ammonium perfluorooctane sulfonate to the reactor, start stirring, control the speed at 300-500rpm, dissolve 3 parts by mass of trimethyl phosphate in 10-15 parts by mass of methanol, and then add the reactor, then close the reactor, introduce nitrogen to replace the air in the reactor 3-5 times, and then introduce carbon monoxide to raise the pressure in the reactor to 3.5-5MPa; b. Turn on the heating device, raise the temperature to 190-220°C, and maintain the reaction for 6-10 hours. During this period, continue stirring to ensure uniform reaction. At the same time, continuously add carbon monoxide through the pressure control system to maintain stable reaction pressure; c. After the reaction is completed, stop heating, close the carbon monoxide inlet valve, cool the reactor naturally to 80-100°C, open the reactor, and filter the reaction liquid through a filter; d. The filtered solution is transferred to a distillation apparatus and distilled under a vacuum degree of 5-10 KPa. The fraction at 150-200 ° C is collected, which is dimethyl 2,6-naphthalene dicarboxylate containing the modified component.

[0010] The naphthalene in step a needs to be dried in a vacuum oven at 80-100°C for 4-6 hours before being added; the amount of nano-silicon dioxide added is 2 parts by mass. Before adding methanol to the reactor, 4A molecular sieve is used for water removal pretreatment, and 100g of 4A molecular sieve is added to each liter of methanol for a treatment time of not less than 24 hours to ensure that the moisture content in methanol is less than 0.01%. For the solid raw materials of pyromellitic anhydride and dimethyl adipate, they are first dried in a drying oven at 80-100°C for 2-4 hours before use to remove adsorbed moisture and a small amount of volatile impurities, ensure the purity of the raw materials, and provide a good foundation for subsequent reactions.

[0011] The cardanol is 3-pentadecylphenol, the organic nucleating agent is di(3,4-dimethylbenzylidene) sorbitol, the composite heat stabilizer is prepared from antioxidant 1010 and tri(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:(1.5-2), the halogen flame retardant is decabromodiphenylethane, the antioxidant is antioxidant 168, and the antistatic agent is stearyl trimethylammonium chloride.

[0012] Preparation method of composite heat stabilizer: Dry the mixed antioxidant 1010 and tris(2,4-di-tert-butylphenyl) phosphite separately. Place antioxidant 1010 in a vacuum oven and dry it for 2-4 hours at a temperature of 60-80°C and a vacuum degree of 0.08-0.09MPa to remove adsorbed moisture. Similarly, tris(2,4-di-tert-butylphenyl) phosphite is also dried in a similar manner, at a slightly lower temperature of 50-70°C, a vacuum degree of 0.08-0.09MPa, and a drying time of 2-3 hours. Add antioxidant 1010 and tris(2,4-di-tert-butylphenyl) phosphite in a twin-screw extruder according to a predetermined mass ratio. First, the twin screws are preheated to 80-100°C, the screw speed is set to 100-200rpm, and the two antioxidants are added from different feed ports. Through the shearing and conveying action of the screws, they are evenly mixed in the extruder. After extrusion, the composite heat stabilizer is obtained through cooling, pelletizing and other operations.

[0013] The method for preparing the composite catalyst solution comprises the following steps: ① Preparation of zinc acetate solution and tetraisopropyl titanate solution: Weigh 10 parts by mass of zinc acetate and 15 parts by mass of tetraisopropyl titanate, and place them in two clean and dry stoppered glass bottles A and B respectively; add 75 parts by mass of toluene to bottle A containing zinc acetate, place bottle A on a magnetic stirrer, adjust the speed to 400 rpm, and stir for 12 minutes; add 75 parts by mass of toluene to bottle B containing tetraisopropyl titanate, also place it on a magnetic stirrer, and stir at 400 rpm for 12 minutes to completely dissolve the tetraisopropyl titanate; ② Preparation of dibutyltin dilaurate solution: weigh 8 parts by mass of dibutyltin dilaurate and put it into a clean stoppered glass bottle C; add 120 parts by mass of acetone, place the glass bottle C on a magnetic stirrer, adjust the speed of the magnetic stirrer to 500 rpm, and stir for 18 minutes; ③ Preparation of antimony trioxide dispersion: Weigh 10 parts by mass of antimony trioxide and 0.6 parts by mass of sodium dodecylbenzene sulfonate, and put them into a stoppered glass bottle D containing 180 parts by mass of deionized water; put the glass bottle D into an ultrasonic cleaner, adjust the ultrasonic power to 300 W, and the ultrasonic time to 25 min; ④ Mixing the composite catalyst: Mix the zinc acetate solution and tetraisopropyl titanate solution in bottles A and B in a clean three-necked flask, place on a magnetic stirrer, and stir at a speed of 300 rpm for 8 minutes; use a dropping funnel to drop the dibutyltin dilaurate solution in bottle C into the three-necked flask at a rate of 1.5 drops / s, and continue stirring during the dropping process. After the dropping is completed, keep the stirring speed at 300 rpm and continue stirring for 12 minutes. Add the antimony trioxide dispersion in bottle D to the three-necked flask at a rate of 0.8 drops / s, and add 1.54 parts by mass of polyvinyl pyrrolidone as a high molecular polymer dispersant; after the addition is completed, keep the stirring speed at 300 rpm and stir for 25 minutes to obtain a preliminary composite catalyst solution; ⑤ Add 0.66 parts by mass of disodium ethylenediaminetetraacetate to the preliminary composite catalyst solution, and stir on a magnetic stirrer at a speed of 300 rpm for 7 minutes to obtain a composite catalyst solution.

[0014] Polyethylene naphthalate is prepared by the above-mentioned method for preparing polyethylene naphthalate.

[0015] The polyethylene naphthalate is used for preparing flexible printed circuit boards for automotive electronic control systems.

[0016] The method for preparing the flexible printed circuit board of the automotive electronic control system comprises the following steps: Ⅰ. Raw material pretreatment: Drying of polyethylene naphthalate: Spread polyethylene naphthalate on a tray of a vacuum oven to ensure uniform thickness of 2-3 cm, start the vacuum oven, evacuate to a pressure of ≤0.01 MPa, heat to 135°C, and dry for 5 hours; Weigh 8 parts by mass of silicon dioxide, disperse it in 100 parts by mass of anhydrous ethanol, add 0.16 parts by mass of γ-aminopropyltriethoxysilane, place the mixed solution in a three-necked flask with a condensation reflux device, put it into a constant temperature water bath, heat it to 70°C, turn on the magnetic stirring, control the speed at 300rpm, react for 3h, after the reaction is completed, filter it with a Buchner funnel, wash it with anhydrous ethanol 3 times, each time with 50 parts by mass, and then place the filter cake in a vacuum oven, dry it at 80°C and pressure ≤0.01MPa for 3h; weigh 6 parts by mass of aluminum oxide, disperse it in 80 parts by mass of anhydrous ethanol, add 0.3 parts by mass of γ-aminopropyltriethoxysilane, stir and react at 75°C and a magnetic stirring speed of 350rpm for 2.5h, and the filtering, washing and drying conditions are the same as those for silicon dioxide treatment; Ⅱ. Mixing: Start the twin-screw extruder, preheat to 290℃, set the screw speed to 250rpm, add the pretreated polyethylene naphthalate first, wait for it to melt in the screw and mix evenly, then start adding the compound raw materials in sequence; The order of addition is: first add the surface-modified silica, keep the screw speed at 250rpm for 2min; then add the surface-modified alumina, stir for 2min at the same screw speed; then add the hyperbranched macromolecular flame-retardant carbon-forming agent and ammonium polyphosphate, increase the screw speed to 300rpm, and stir for 3min; then add the carboxyl-terminated nitrile rubber, keep the screw speed at 300rpm, and stir for 2min; finally, according to the circuit design requirements, if conductive fillers need to be added, add carbon nanotubes or silver powder, adjust the screw speed to 350rpm, stir for 3min, and the total duration of the entire mixing process is controlled within 20min; the hyperbranched macromolecular flame-retardant carbon-forming agent is Realgard™ 9898; III. Molding Processing - Melt Extrusion Process: The mixed materials are conveyed to the extruder hopper through a screw conveyor. The extruder is divided into 5 heating zones from the hopper end to the head end. The temperature settings of each zone are: 295℃, 300℃, 305℃, 305℃, 310℃; the extrusion pressure is 20-30MPa; IV. Post-processing: Heat setting treatment: First heat setting: the extruded substrate is passed through a heat setting device with a fixed width. The internal temperature of the device is set to 220°C, the substrate transmission speed is 10cm / s, and the processing time is 15s, so that the substrate initially stabilizes its size and improves its mechanical properties; Second heat setting: the substrate is placed in a hot environment with a temperature of 210°C, and a relaxed suspension method is used to ensure the free shrinkage of the substrate. The processing time is 10s; nitrogen is introduced into the heat setting device for protection, and the nitrogen flow rate is controlled at 10-20L / min; Surface modification-plasma treatment: The formed substrate is placed in a vacuum chamber of a plasma treatment device, evacuated to a pressure of ≤0.005 MPa, oxygen plasma is selected, the gas flow rate is controlled at 30 mL / min, the plasma is excited by a radio frequency power supply, the processing power is 200 W, and the processing time is 60 s, thereby obtaining a flexible printed circuit board for an automotive electronic control system.

[0017] In the process of preparing the flexible printed circuit board for the automotive electronic control system, the selection and mass fraction of each raw material are as follows: Polyethylene naphthalate: 100 parts; Silicon dioxide: fumed silicon dioxide with a particle size of 5-15 μm, 8 parts; Alumina: γ-alumina with an average particle size of 3-5 μm, 6 parts; Hyperbranched macromolecular flame retardant carbon-forming agent: weight average molecular weight is 10000-15000, 10 parts; Ammonium polyphosphate: degree of polymerization n is between 500-800, 15 parts; Carboxyl-terminated nitrile rubber: acrylonitrile content is 20-30%, 7 parts; Carbon nanotubes: multi-walled carbon nanotubes with a diameter of 5-20 nm and a length of 5-20 μm, 1.5 parts; Silver powder: spherical silver powder with an average particle size of 1-5μm, purity ≥99.9%, 3 parts.

[0018] Naphthalene, as the basic reactant, undergoes carbonylation reaction in the presence of methanol and carbon monoxide. Methanol serves as a reaction solvent on the one hand, and provides the hydroxyl groups required for the formation of esters on the other. Carbon monoxide inserts into the aromatic ring of naphthalene under high pressure and reacts with methanol to form an ester bond to form dimethyl 2,6-naphthalenedicarboxylate. The reaction principle is based on the carbonylation reaction mechanism. Under the action of high temperature, high pressure and catalyst, the carbon of carbon monoxide combines with the active site on the naphthalene ring, and then reacts with the hydroxyl group of methanol to form an ester. Nano-silica plays a major role in physical and chemical modification in the reaction system. Physically, it can fill between the generated product molecules to increase the stability of the system. Chemically, the hydroxyl groups on its surface can form weak interactions such as hydrogen bonds with other components in the system (such as dimethyl 2,6-naphthalenedicarboxylate) to improve the performance of the product, such as barrier properties. The anhydride groups in pyromellitic anhydride can react with active groups such as hydroxyl groups on the intermediates or product molecules generated during the reaction to form a cross-linked structure. This cross-linking can increase the interaction between molecular chains and limit the movement of molecular chains, thereby enhancing the thermal stability of subsequent polyethylene naphthalate. The ester group and the longer carbon chain in the molecular structure of dimethyl adipate can be inserted between the molecular chains of the reaction product, playing a role in plasticization and toughening. When the material is subjected to external force, the dimethyl adipate molecules can make it easier for the molecular chains to slide and absorb energy, thereby improving the mechanical properties. The fluorine atoms in ammonium perfluorooctane sulfonate have strong electronegativity, which makes the molecule highly chemically stable. In the material system, it can form a protective film on the surface of the material, or interact with the molecular chain of the material to prevent the erosion of chemical substances, thereby improving the chemical stability of the material. After the subsequent polymerization reaction or material molding, trimethyl phosphate can migrate to the surface of the material and capture electrons through the characteristics of its phosphate group, thereby reducing the generation of static electricity and improving the antistatic properties of the material.

[0019] After zinc acetate and tetraisopropyl titanate are dissolved in the organic solvent toluene, zinc ions and titanate molecules can form complexes or active centers in the solution. In the catalytic reaction, these active centers can interact with the reactant molecules (such as esters and alcohols in the transesterification reaction), reduce the activation energy of the reaction through coordination, oxidation-reduction and other processes, and promote the reaction. The different ratios between them will affect the structure and number of active centers, thereby affecting the activity and selectivity of the catalyst. After dibutyltin dilaurate is dissolved in acetone, the tin atoms in its molecules have empty orbitals, which can interact with the lone pairs of electrons in the reactant molecules. In the synthesis reaction of polyethylene naphthalate, it can promote the transesterification reaction, especially the reaction between hydroxyl-containing reactants (such as ethylene glycol) and esters (such as 2,6-naphthalene dicarboxylic acid dimethyl ester). Antimony trioxide forms a dispersed system with sodium dodecylbenzene sulfonate in water. As a surfactant, sodium dodecylbenzene sulfonate can adsorb its hydrophobic alkyl chain on the surface of antimony trioxide, while the hydrophilic sulfonate group can disperse the particles in water. In the composite catalyst system, antimony trioxide can play a synergistic catalytic role. Its specific catalytic mechanism may be related to its oxidation-reduction properties. In some reaction processes, it can regulate the electron transfer process of the reaction system and improve the overall performance of the catalyst. As a high molecular polymer dispersant, polyvinylpyrrolidone (PVP) can adsorb on the surface of catalyst particles during the mixing process of the composite catalyst to prevent particle agglomeration and ensure that all components are fully mixed. As a metal chelator, disodium ethylenediaminetetraacetate (EDTA-2Na) can form stable chelates with metal ions (such as zinc ions, tin ions, etc.) in the solution after addition, preventing unnecessary interactions between metal ions and improving the stability of the catalyst.

[0020] The main chain structure of polyethylene naphthalate is generated by transesterification of 2,6-dimethyl naphthalate and ethylene glycol containing modified components. During the reaction, the hydroxyl group of ethylene glycol reacts with the ester group of 2,6-dimethyl naphthalate to gradually form a polyester chain. The copolymerization of terephthalic acid, pyromellitic anhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride and ethylene glycol can change the molecular chain structure and properties of the polymer. They can introduce different aromatic ring structures and functional groups to increase the rigidity and regularity of the molecular chain, thereby improving the thermal and mechanical properties of the material. At the same time, different acid structures can adjust the crystallization properties of the polymer and affect the transparency, hardness and other properties of the material. The cardanol molecule contains phenolic hydroxyl groups and long carbon chain alkyl groups. The phenolic hydroxyl groups can react with the carboxyl groups or acid anhydride groups in the polyester chain to introduce long carbon chain alkyl groups into the polymer molecular chain. Long carbon chain alkyl can increase the distance between molecular chains, reduce the interaction between molecular chains, play a role in toughening and plasticizing, and may also improve the flexibility and processing performance of the material. Di (3, 4-dimethylbenzylidene) sorbitol (DMDBS) can provide effective nucleation sites to promote the formation of more, finer and uniform grains of polyethylene naphthalate (PEN) during the crystallization process. This helps to increase the crystallization rate of the material and shorten the molding cycle. At the same time, the refined grain structure can enhance the transparency, hardness and tensile strength of the material. Hindered phenol antioxidant 1010 can capture free radicals to prevent polymers from being degraded by oxidation during high-temperature processing or use. Phosphite auxiliary antioxidants can decompose hydroperoxides and inhibit the chain reaction of oxidation reactions. After the two are compounded, they work synergistically to more effectively inhibit the thermal oxidation degradation of PEN during thermal processing and improve the thermal stability and long-term performance of the material. During the melt processing of PEN, the composite heat stabilizer can prevent the material from turning yellow and brittle due to high temperature, maintain the mechanical properties and appearance color of the material, and extend the service life of the material. During the reaction, decabromodiphenylethane can decompose to produce bromine free radicals, which can react with highly active free radicals (such as hydrogen free radicals and hydroxyl free radicals) produced during the reaction, thereby interrupting the chain reaction. When the organic nucleating agent and the composite heat stabilizer are compounded, the organic nucleating agent promotes crystallization and makes the internal structure of the material more regular, while the composite heat stabilizer can stabilize the molecular chain structure of the material during the crystallization process to prevent thermal oxidation degradation during the crystallization process. The two work together to improve the thermal and mechanical properties of the material. When the halogen flame retardant and the antioxidant are compounded, the halogen flame retardant prevents the spread of flames, and the antioxidant prevents the material from accelerating degradation due to oxidation at high temperatures (high temperatures are also involved in the reaction process), thereby improving the overall performance of the material in a fire scenario. Antistatic agents also have synergistic effects with other additives. While ensuring the antistatic properties of the material, they do not affect the improvement of the material properties by other additives. For example, the antistatic agent will not interfere with the nucleation process of the organic nucleating agent, nor will it reduce the flame retardant effect of the flame retardant.

[0021] The effective ingredients in the composite catalyst solution (such as zinc acetate-tetraisopropyl titanate complex, dibutyltin dilaurate, etc.) can promote the transesterification reaction through coordination, nucleophilic-electrophilic reaction mechanisms, reduce the activation energy of the reaction, and enable the reaction to proceed smoothly at lower temperatures and pressures. In the polycondensation reaction stage, the catalyst can also promote the removal of small molecules (such as ethylene glycol) from the reaction system and increase the molecular weight of the polymer.

[0022] As inorganic fillers, silica and alumina can be filled between the resin molecular chains after being mixed with polyethylene naphthalate. On the one hand, they can limit the movement of the resin molecular chains through physical hindrance, thereby improving the rigidity and dimensional stability of the material; on the other hand, they have high thermal conductivity and low thermal expansion coefficient, and can work synergistically with polyethylene naphthalate to absorb and disperse heat in a high temperature environment, reduce the thermal expansion coefficient of the material, and improve the heat resistance and electrical insulation properties of the material. Hyperbranched macromolecular flame retardant carbon former and ammonium polyphosphate are compounded in a specific ratio to form an intumescent flame retardant system. During the reaction, ammonium polyphosphate decomposes to produce acidic substances such as phosphoric acid, which can catalyze the dehydration of the hyperbranched macromolecular flame retardant carbon former into carbon. The formed carbon layer can cover the surface of the material, play a role in heat insulation and oxygen isolation, prevent the spread of flames, and also prevent further decomposition and reaction of internal materials, thereby improving the flame retardant properties of the material. Polyethylene naphthalate and carboxyl-terminated nitrile rubber interact through chemical reactions (such as the reaction of carboxyl groups with hydroxyl or ester groups) and physical entanglement. The elastic segments of the toughening agent can interpenetrate with the polyethylene naphthalate molecular chains. When the material is subjected to external forces, the toughening agent can absorb energy through its own deformation, thereby improving the toughness of the material. Carbon nanotubes and silver powder can form conductive connections in the polyethylene naphthalate matrix. Carbon nanotubes have a unique one-dimensional nanostructure and good conductivity, and can form a conductive network at a low addition amount; silver powder has excellent conductivity and can play a role in situations where higher conductivity is required. Their addition can give the material a certain conductivity to meet the functional requirements of electromagnetic shielding in automotive electronic control systems.

[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) Excellent performance in thermal performance. By adding polyacids or anhydrides such as pyromellitic anhydride and 1,4,5,8-naphthalenetetracarboxylic anhydride to the main raw materials, more rigid aromatic ring structures are introduced, and the regularity of the molecular chain is enhanced, which greatly improves the heat resistance of the material and can adapt to the complex and high-temperature working environment of automotive electronic control systems. At the same time, the addition of inorganic fillers such as nano-silica and alumina, with their own low thermal expansion coefficient and high heat resistance, fills the polymer molecular chains, which not only effectively restricts the movement of the molecular chains, reduces the thermal expansion coefficient, and prevents the product from deformation, cracking and other problems under temperature changes, but also synergistically improves the overall heat resistance and ensures the stable operation of the product under high temperature conditions.

[0024] (2) Mechanical properties are enhanced. The introduction of cardanol is a key link. The phenolic hydroxyl group in its molecule reacts with the polyester chain, and the long carbon chain alkyl is integrated into the molecular chain, increasing the distance between the molecular chains, playing a toughening and plasticizing effect, giving the material good flexibility and impact resistance, and avoiding damage due to external force impact during processing and subsequent use. Silica and alumina, as inorganic fillers, not only enhance heat resistance, but also significantly improve the rigidity and dimensional stability of the material, ensuring the precise dimensional requirements of the product and meeting the strict requirements of flexible printed circuit boards for structural strength and stability.

[0025] (3) Excellent flame retardant properties. Hyperbranched macromolecular flame retardant carbonizing agent and ammonium polyphosphate are compounded in a specific ratio to form an intumescent flame retardant system. When encountering a fire source, ammonium polyphosphate decomposes to produce acidic substances that catalyze the carbonizing agent to dehydrate into carbon, quickly forming a dense heat-insulating and oxygen-isolating carbon layer on the surface of the material, effectively preventing the spread of flames, greatly reducing the risk of fire, and safeguarding the safe operation of automotive electronic systems.

[0026] (4) Excellent antistatic performance. Trimethyl phosphate can migrate to the surface of the material after molding to capture electrons and reduce static electricity generation. The antistatic agent absorbs environmental moisture to form a conductive water film or conducts ions by itself, which can promptly conduct away static electricity and prevent static electricity accumulation from damaging electronic components, thus ensuring the normal operation of the automotive electronic control system.

[0027] (5) Excellent performance in surface properties and processing properties. Pretreatment of PEN resin and inorganic filler improves the compatibility between raw materials, making mixing more uniform and processing smoother. Plasma treatment introduces polar groups such as hydroxyl and carboxyl groups on the surface of the substrate, which not only improves the surface roughness and increases the adhesion with adhesives and metal coatings, facilitating subsequent circuit board production, but also optimizes the surface activity of the material, which is conducive to fine processing and ensures the production of high-quality flexible printed circuit boards to meet the complex and precise process requirements of automotive electronic control systems. DETAILED DESCRIPTION

[0028] In order to make the purpose and technical solution of the present invention more clear, the present invention is further described in detail below.

[0029] In the following embodiments: The preparation method of the composite heat stabilizer used is: the antioxidant 1010 and tris (2, 4-di-tert-butylphenyl) phosphite to be mixed are dried separately, and the antioxidant 1010 is placed in a vacuum oven and dried for 3 hours at a temperature of 70°C and a vacuum degree of 0.08MPa to remove the adsorbed moisture. Similarly, tris (2, 4-di-tert-butylphenyl) phosphite is also subjected to the same drying treatment, at a temperature of 60°C, a vacuum degree of 0.08MPa, and a drying time of 2-3h. In a twin-screw extruder, antioxidant 1010 and tris (2, 4-di-tert-butylphenyl) phosphite are added according to a predetermined mass ratio. First, the twin screw is preheated to 90°C, the screw speed is set to 150rpm, and the two antioxidants are added from different feed ports. Through the shearing and conveying action of the screw, they are evenly mixed in the extruder. After extrusion, the composite heat stabilizer is obtained through cooling, pelletizing and other operations.

[0030] In step a, before adding methanol to the reactor, 4A molecular sieve is used for dehydration pretreatment, 100 g of 4A molecular sieve is added to each liter of methanol, and the treatment time is 24 hours; for the solid raw materials, pyromellitic dianhydride and dimethyl adipate, they are dried in a drying oven at 90° C. for 3 hours before use.

[0031] The hyperbranched macromolecular flame retardant carbon-forming agent is Realgard™ 9898.

[0032] Example 1 The preparation method of dimethyl 2,6-naphthalene dicarboxylate containing a modified component comprises the following steps: a. Add the nano-silica suspension to the reactor, then add 100 parts by mass of naphthalene, 200 parts by mass of methanol, 5 parts by mass of pyromellitic anhydride, 10 parts by mass of dimethyl adipate and 0.5 parts by mass of ammonium perfluorooctane sulfonate to the reactor, start stirring, control the speed at 400 rpm, dissolve 3 parts by mass of trimethyl phosphate in 12 parts by mass of methanol, and then add the reactor, then close the reactor, introduce nitrogen to replace the air in the reactor 4 times, and then introduce carbon monoxide to raise the pressure in the reactor to 4 MPa; b. Turn on the heating device, raise the temperature to 200°C, and maintain the reaction for 8 hours. During this period, continue stirring to ensure uniform reaction. At the same time, continuously add carbon monoxide through the pressure control system to maintain stable reaction pressure; c. After the reaction is completed, stop heating, close the carbon monoxide inlet valve, cool the reactor naturally to 90°C, open the reactor, and filter the reaction liquid through a filter; d. The filtered solution was transferred to a distillation apparatus and distilled under a vacuum of 8 KPa. The fraction at 180 ° C was collected, which was dimethyl 2,6-naphthalene dicarboxylate containing the modified component.

[0033] The naphthalene in step a needs to be dried in a vacuum oven at 90° C. for 5 h before being added; the amount of nano-silicon dioxide added is 2 parts by mass.

[0034] The method for preparing the composite catalyst solution comprises the following steps: ① Preparation of zinc acetate solution and tetraisopropyl titanate solution: Weigh 10 parts by mass of zinc acetate and 15 parts by mass of tetraisopropyl titanate, and place them in two clean and dry stoppered glass bottles A and B respectively; add 75 parts by mass of toluene to bottle A containing zinc acetate, place bottle A on a magnetic stirrer, adjust the speed to 400 rpm, and stir for 12 minutes; add 75 parts by mass of toluene to bottle B containing tetraisopropyl titanate, also place it on a magnetic stirrer, and stir at 400 rpm for 12 minutes to completely dissolve the tetraisopropyl titanate; ② Preparation of dibutyltin dilaurate solution: weigh 8 parts by mass of dibutyltin dilaurate and put it into a clean stoppered glass bottle C; add 120 parts by mass of acetone, place the glass bottle C on a magnetic stirrer, adjust the speed of the magnetic stirrer to 500 rpm, and stir for 18 minutes; ③ Preparation of antimony trioxide dispersion: Weigh 10 parts by mass of antimony trioxide and 0.6 parts by mass of sodium dodecylbenzene sulfonate, and put them into a stoppered glass bottle D containing 180 parts by mass of deionized water; put the glass bottle D into an ultrasonic cleaner, adjust the ultrasonic power to 300 W, and the ultrasonic time to 25 min; ④ Mixing the composite catalyst: Mix the zinc acetate solution and tetraisopropyl titanate solution in bottles A and B in a clean three-necked flask, place on a magnetic stirrer, and stir at a speed of 300 rpm for 8 minutes; use a dropping funnel to drop the dibutyltin dilaurate solution in bottle C into the three-necked flask at a rate of 1.5 drops / s, and continue stirring during the dropping process. After the dropping is completed, keep the stirring speed at 300 rpm and continue stirring for 12 minutes. Add the antimony trioxide dispersion in bottle D to the three-necked flask at a rate of 0.8 drops / s, and add 1.54 parts by mass of polyvinyl pyrrolidone as a high molecular polymer dispersant; after the addition is completed, keep the stirring speed at 300 rpm and stir for 25 minutes to obtain a preliminary composite catalyst solution; ⑤ Add 0.66 parts by mass of disodium ethylenediaminetetraacetate to the preliminary composite catalyst solution, and stir on a magnetic stirrer at a speed of 300 rpm for 7 minutes to obtain a composite catalyst solution.

[0035] The preparation method of polyethylene naphthalate comprises the following steps: (1) 100 parts of 2,6-naphthalene dicarboxylic acid dimethyl ester containing a modified component, 70 parts of ethylene glycol, 20 parts of terephthalic acid, 10 parts of pyromellitic anhydride and 10 parts of 1,4,5,8-naphthalene tetracarboxylic anhydride, 10 parts of cardanol, 0.5 parts of an organic nucleating agent, 3 parts of a composite heat stabilizer, 12 parts of a halogen flame retardant, 0.5 parts of an antioxidant, 1.5 parts of an antistatic agent and a composite catalyst solution are added into a reactor to carry out an ester exchange reaction, wherein the amount of the composite catalyst solution is determined by 0.3% of the mass of 2,6-naphthalene dicarboxylic acid dimethyl ester containing a modified component; heating is performed, the stirring speed is controlled at 130 rpm, the reaction temperature is controlled at 200°C, and the reaction time is 4 hours; (2) After the ester exchange reaction is completed, the temperature is raised to 270°C, and the pressure of the reaction system is reduced to 50 Pa to carry out the polycondensation reaction for 2 hours; (3) After the polycondensation reaction is completed, the heating is stopped and the mixture is cooled naturally under nitrogen protection. When the temperature drops to 120°C, the product is discharged from the reactor and pelletized to obtain granular polyethylene naphthalate. Among them, the cardanol is 3-pentadecylphenol, the organic nucleating agent is di(3,4-dimethylbenzylidene) sorbitol, the composite heat stabilizer is prepared from antioxidant 1010 and tri(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:2, the halogen flame retardant is decabromodiphenylethane, the antioxidant is antioxidant 168, and the antistatic agent is stearyl trimethylammonium chloride.

[0036] Example 2 The preparation method of dimethyl 2,6-naphthalene dicarboxylate containing a modified component comprises the following steps: a. Add the nano-silica suspension to the reactor, then add 100 parts by mass of naphthalene, 200 parts by mass of methanol, 5 parts by mass of pyromellitic anhydride, 10 parts by mass of dimethyl adipate and 0.5 parts by mass of ammonium perfluorooctane sulfonate to the reactor, start stirring, control the speed at 300 rpm, dissolve 3 parts by mass of trimethyl phosphate in 10 parts by mass of methanol, and then add the reactor, then close the reactor, introduce nitrogen to replace the air in the reactor 3 times, and then introduce carbon monoxide to raise the pressure in the reactor to 3.5 MPa; b. Turn on the heating device, raise the temperature to 190°C, and maintain the reaction for 6 hours. During this period, continue stirring to ensure uniform reaction. At the same time, continuously add carbon monoxide through the pressure control system to maintain stable reaction pressure; c. After the reaction is completed, stop heating, close the carbon monoxide inlet valve, cool the reactor naturally to 80°C, open the reactor, and filter the reaction liquid through a filter; d. The filtered solution was transferred to a distillation apparatus and distilled under a vacuum of 5 KPa. The fraction at 150 ° C was collected, which was dimethyl 2,6-naphthalene dicarboxylate containing the modified component.

[0037] The naphthalene in step a needs to be dried in a vacuum oven at 80° C. for 4 h before being added; the amount of nano-silicon dioxide added is 2 parts by mass.

[0038] The method for preparing the composite catalyst solution comprises the following steps: ① Preparation of zinc acetate solution and tetraisopropyl titanate solution: Weigh 10 parts by mass of zinc acetate and 15 parts by mass of tetraisopropyl titanate, and place them in two clean and dry stoppered glass bottles A and B respectively; add 75 parts by mass of toluene to bottle A containing zinc acetate, place bottle A on a magnetic stirrer, adjust the speed to 400 rpm, and stir for 12 minutes; add 75 parts by mass of toluene to bottle B containing tetraisopropyl titanate, also place it on a magnetic stirrer, and stir at 400 rpm for 12 minutes to completely dissolve the tetraisopropyl titanate; ② Preparation of dibutyltin dilaurate solution: weigh 8 parts by mass of dibutyltin dilaurate and put it into a clean stoppered glass bottle C; add 120 parts by mass of acetone, place the glass bottle C on a magnetic stirrer, adjust the speed of the magnetic stirrer to 500 rpm, and stir for 18 minutes; ③ Preparation of antimony trioxide dispersion: Weigh 10 parts by mass of antimony trioxide and 0.6 parts by mass of sodium dodecylbenzene sulfonate, and put them into a stoppered glass bottle D containing 180 parts by mass of deionized water; put the glass bottle D into an ultrasonic cleaner, adjust the ultrasonic power to 300 W, and the ultrasonic time to 25 min; ④ Mixing the composite catalyst: Mix the zinc acetate solution and tetraisopropyl titanate solution in bottles A and B in a clean three-necked flask, place on a magnetic stirrer, and stir at a speed of 300 rpm for 8 minutes; use a dropping funnel to drop the dibutyltin dilaurate solution in bottle C into the three-necked flask at a rate of 1.5 drops / s, and continue stirring during the dropping process. After the dropping is completed, keep the stirring speed at 300 rpm and continue stirring for 12 minutes. Add the antimony trioxide dispersion in bottle D to the three-necked flask at a rate of 0.8 drops / s, and add 1.54 parts by mass of polyvinyl pyrrolidone as a high molecular polymer dispersant; after the addition is completed, keep the stirring speed at 300 rpm and stir for 25 minutes to obtain a preliminary composite catalyst solution; ⑤ Add 0.66 parts by mass of disodium ethylenediaminetetraacetate to the preliminary composite catalyst solution, and stir on a magnetic stirrer at a speed of 300 rpm for 7 minutes to obtain a composite catalyst solution.

[0039] The preparation method of polyethylene naphthalate comprises the following steps: (1) 100 parts of 2,6-naphthalene dicarboxylic acid dimethyl ester containing a modified component, 75 parts of ethylene glycol, 30 parts of terephthalic acid, 20 parts of pyromellitic anhydride and 20 parts of 1,4,5,8-naphthalene tetracarboxylic anhydride, 15 parts of cardanol, 1 part of an organic nucleating agent, 5 parts of a composite heat stabilizer, 20 parts of a halogen flame retardant, 1 part of an antioxidant, 3 parts of an antistatic agent and a composite catalyst solution are added into a reactor to carry out an ester exchange reaction, wherein the amount of the composite catalyst solution is determined by 0.5% of the mass of 2,6-naphthalene dicarboxylic acid dimethyl ester containing a modified component; heating is performed, the stirring speed is controlled at 150 rpm, the reaction temperature is controlled at 220°C, and the reaction time is 6 hours; (2) After the transesterification reaction is completed, the temperature is raised to 280°C and the pressure of the reaction system is reduced to 100 Pa to carry out the polycondensation reaction for 3 hours; (3) After the polycondensation reaction is completed, the heating is stopped and the mixture is cooled naturally under nitrogen protection. When the temperature drops to 150°C, the product is discharged from the reactor and pelletized to obtain granular polyethylene naphthalate. Among them, the cardanol is 3-pentadecylphenol, the organic nucleating agent is di(3,4-dimethylbenzylidene) sorbitol, the composite heat stabilizer is prepared from antioxidant 1010 and tri(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:2, the halogen flame retardant is decabromodiphenylethane, the antioxidant is antioxidant 168, and the antistatic agent is stearyl trimethylammonium chloride.

[0040] Example 3 The preparation method of dimethyl 2,6-naphthalene dicarboxylate containing a modified component comprises the following steps: a. Add the nano-silica suspension to the reactor, then add 100 parts by mass of naphthalene, 200 parts by mass of methanol, 5 parts by mass of pyromellitic anhydride, 10 parts by mass of dimethyl adipate and 0.5 parts by mass of ammonium perfluorooctane sulfonate to the reactor, start stirring, control the speed at 500 rpm, dissolve 3 parts by mass of trimethyl phosphate in 15 parts by mass of methanol, and then add the reactor, then close the reactor, introduce nitrogen to replace the air in the reactor 5 times, and then introduce carbon monoxide to raise the pressure in the reactor to 5 MPa; b. Turn on the heating device, raise the temperature to 220°C, and maintain the reaction for 10 hours. During this period, continue stirring to ensure uniform reaction. At the same time, continuously add carbon monoxide through the pressure control system to maintain stable reaction pressure; c. After the reaction is completed, stop heating, close the carbon monoxide inlet valve, cool the reactor naturally to 100°C, open the reactor, and filter the reaction liquid through a filter; d. The filtered solution was transferred to a distillation apparatus and distilled under a vacuum of 10 KPa. The fraction at 200 ° C was collected, which was dimethyl 2,6-naphthalene dicarboxylate containing the modified component.

[0041] The naphthalene in step a needs to be dried in a vacuum oven at 100° C. for 6 hours before being added; the amount of nano-silicon dioxide added is 2 parts by mass.

[0042] The method for preparing the composite catalyst solution comprises the following steps: ① Preparation of zinc acetate solution and tetraisopropyl titanate solution: Weigh 10 parts by mass of zinc acetate and 15 parts by mass of tetraisopropyl titanate, and place them in two clean and dry stoppered glass bottles A and B respectively; add 75 parts by mass of toluene to bottle A containing zinc acetate, place bottle A on a magnetic stirrer, adjust the speed to 400 rpm, and stir for 12 minutes; add 75 parts by mass of toluene to bottle B containing tetraisopropyl titanate, also place it on a magnetic stirrer, and stir at 400 rpm for 12 minutes to completely dissolve the tetraisopropyl titanate; ② Preparation of dibutyltin dilaurate solution: weigh 8 parts by mass of dibutyltin dilaurate and put it into a clean stoppered glass bottle C; add 120 parts by mass of acetone, place the glass bottle C on a magnetic stirrer, adjust the speed of the magnetic stirrer to 500 rpm, and stir for 18 minutes; ③ Preparation of antimony trioxide dispersion: Weigh 10 parts by mass of antimony trioxide and 0.6 parts by mass of sodium dodecylbenzene sulfonate, and put them into a stoppered glass bottle D containing 180 parts by mass of deionized water; put the glass bottle D into an ultrasonic cleaner, adjust the ultrasonic power to 300 W, and the ultrasonic time to 25 min; ④ Mixing the composite catalyst: Mix the zinc acetate solution and tetraisopropyl titanate solution in bottles A and B in a clean three-necked flask, place on a magnetic stirrer, and stir at a speed of 300 rpm for 8 minutes; use a dropping funnel to drop the dibutyltin dilaurate solution in bottle C into the three-necked flask at a rate of 1.5 drops / s, and continue stirring during the dropping process. After the dropping is completed, keep the stirring speed at 300 rpm and continue stirring for 12 minutes. Add the antimony trioxide dispersion in bottle D to the three-necked flask at a rate of 0.8 drops / s, and add 1.54 parts by mass of polyvinyl pyrrolidone as a high molecular polymer dispersant; after the addition is completed, keep the stirring speed at 300 rpm and stir for 25 minutes to obtain a preliminary composite catalyst solution; ⑤ Add 0.66 parts by mass of disodium ethylenediaminetetraacetate to the preliminary composite catalyst solution, and stir on a magnetic stirrer at a speed of 300 rpm for 7 minutes to obtain a composite catalyst solution.

[0043] The preparation method of polyethylene naphthalate comprises the following steps: (1) 100 parts of 2,6-naphthalene dicarboxylic acid dimethyl ester containing a modified component, 60 parts of ethylene glycol, 10 parts of terephthalic acid, 5 parts of pyromellitic anhydride and 5 parts of 1,4,5,8-naphthalene tetracarboxylic anhydride, 5 parts of cardanol, 0.05 parts of an organic nucleating agent, 1 part of a composite heat stabilizer, 8 parts of a halogen flame retardant, 0.1 parts of an antioxidant, 0.5 parts of an antistatic agent and a composite catalyst solution are added into a reactor to carry out an ester exchange reaction, wherein the amount of the composite catalyst solution is determined by 0.05% of the mass of 2,6-naphthalene dicarboxylic acid dimethyl ester containing a modified component; heating is performed, the stirring speed is controlled at 120 rpm, the reaction temperature is controlled at 180°C, and the reaction time is 2 hours; (2) After the ester exchange reaction is completed, the temperature is raised to 260°C, and the pressure of the reaction system is reduced to 10Pa to carry out the polycondensation reaction for 1 hour; (3) After the polycondensation reaction is completed, the heating is stopped and the mixture is cooled naturally under nitrogen protection. When the temperature drops to 100°C, the product is discharged from the reactor and pelletized to obtain granular polyethylene naphthalate. Among them, the cardanol is 3-pentadecylphenol, the organic nucleating agent is di(3,4-dimethylbenzylidene) sorbitol, the composite heat stabilizer is prepared from antioxidant 1010 and tri(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:1.5, the halogen flame retardant is decabromodiphenylethane, the antioxidant is antioxidant 168, and the antistatic agent is stearyl trimethylammonium chloride.

[0044] Comparative Example 1, Compared with Example 1, the difference is that no nano silicon dioxide and pyromellitic dianhydride are added.

[0045] Comparative Example 2 Compared with Example 1, the difference is that dimethyl adipate and trimethyl phosphate are not added.

[0046] Comparative Example 3 Compared with Example 1, the difference is that tetraisopropyl titanate and antimony trioxide are not added, and the amount of zinc acetate used is the sum of the masses of zinc acetate and tetraisopropyl titanate in Example 1.

[0047] Comparative Example 4 Compared with Example 2, the difference is that terephthalic acid and 1,4,5,8-naphthalenetetracarboxylic dianhydride are not added, and the added amount of pyromellitic dianhydride is the sum of the masses of terephthalic acid, pyromellitic dianhydride and 1,4,5,8-naphthalenetetracarboxylic dianhydride in Example 2.

[0048] Comparative Example 5 Compared with Example 3, the difference is that cardanol and composite heat stabilizer are not added.

[0049] The test data of Examples 1-3 and Comparative Examples 1-5 are shown in Table 1.

[0050] Table 1: Test data of Examples 1-3 and Comparative Examples 1-5

[0051] From the above data, it can be seen that the polyethylene naphthalate prepared by the preparation method provided by the present invention has excellent performance, and the thermal properties, mechanical properties, flame retardant properties and antistatic properties are greatly improved, meeting the needs of industrial production.

[0052] Application Example 1 In the process of preparing flexible printed circuit boards for automotive electronic control systems, the selection and mass fraction of each raw material are as follows: Polyethylene naphthalate obtained in Example 1: 100 parts; Silicon dioxide: fumed silicon dioxide with a particle size of 10 μm, 8 parts; Alumina: γ-alumina with an average particle size of 4 μm, 6 parts; Hyperbranched macromolecular flame retardant carbon-forming agent: weight average molecular weight is 12000, 10 parts; Ammonium polyphosphate: degree of polymerization n is 650, 15 parts; Carboxyl-terminated nitrile rubber: acrylonitrile mass content is 25%, 7 parts.

[0053] A method for preparing a flexible printed circuit board for an automotive electronic control system comprises the following steps: Ⅰ. Raw material pretreatment: Drying the polyethylene naphthalate: Spread the polyethylene naphthalate obtained in Example 1 on a tray of a vacuum oven to ensure uniform thickness at 3 cm, start the vacuum oven, evacuate to a pressure of 0.01 MPa, raise the temperature to 135° C., and dry for 5 h; Weigh 8 parts by mass of silicon dioxide, disperse it in 100 parts by mass of anhydrous ethanol, add 0.16 parts by mass of γ-aminopropyltriethoxysilane, place the mixed solution in a three-necked flask with a condensation reflux device, put it into a constant temperature water bath, heat it to 70°C, turn on the magnetic stirring, control the speed at 300rpm, react for 3h, after the reaction is completed, filter it with a Buchner funnel, wash it with anhydrous ethanol 3 times, each time with 50 parts by mass, and then place the filter cake in a vacuum oven and dry it at 80°C and 0.01MPa for 3h; weigh 6 parts by mass of aluminum oxide, disperse it in 80 parts by mass of anhydrous ethanol, add 0.3 parts by mass of γ-aminopropyltriethoxysilane, stir and react at 75°C and 350rpm of magnetic stirring speed for 2.5h, and the filtering, washing and drying conditions are the same as those for silicon dioxide treatment; Ⅱ. Mixing: Start the twin-screw extruder, preheat to 290℃, set the screw speed to 250rpm, add the pretreated polyethylene naphthalate first, wait for it to melt in the screw and mix evenly, then start adding the compound raw materials in sequence; The order of addition is as follows: first add the surface-modified silica, keep the screw speed at 250rpm for 2min; then add the surface-modified alumina, stir for 2min at the same screw speed; then add the hyperbranched macromolecular flame-retardant carbonizing agent and ammonium polyphosphate, increase the screw speed to 300rpm, stir for 3min; then add the carboxyl-terminated nitrile rubber, keep the screw speed at 300rpm, stir for 2min; III. Molding process - melt extrusion process: The mixed materials are conveyed to the extruder hopper through a screw conveyor. The extruder is divided into 5 heating zones from the hopper end to the head end. The temperature settings of each zone are: 295℃, 300℃, 305℃, 305℃, 310℃; the extrusion pressure is 25MPa; IV. Post-processing: Heat setting treatment: primary heat setting: the extruded substrate is passed through a heat setting device with a fixed width, the internal temperature of the device is set to 220°C, the substrate transmission speed is 10cm / s, and the treatment time is 15s, so that the substrate initially stabilizes its size and improves its mechanical properties; secondary heat setting: the substrate is placed in a hot environment with a temperature of 210°C, a relaxed suspension method is used to ensure the substrate's free shrinkage, and the treatment time is 10s; nitrogen is introduced into the heat setting device for protection, and the nitrogen flow rate is controlled at 15L / min; Surface modification-plasma treatment: The formed substrate is placed in a vacuum chamber of a plasma treatment device, evacuated to a pressure of 0.005 MPa, oxygen plasma is selected, the gas flow rate is controlled at 30 mL / min, the plasma is excited by a radio frequency power supply, the processing power is 200 W, and the processing time is 60 s, thereby obtaining a flexible printed circuit board for an automotive electronic control system.

[0054] Application Example 2 In the process of preparing flexible printed circuit boards for automotive electronic control systems, the selection and mass fraction of each raw material are as follows: Polyethylene naphthalate obtained in Example 1: 100 parts; Silicon dioxide: fumed silicon dioxide with a particle size of 5 μm, 8 parts; Alumina: γ-alumina with an average particle size of 3 μm, 6 parts; Hyperbranched macromolecular flame retardant carbon-forming agent: weight average molecular weight is 10000, 10 parts; Ammonium polyphosphate: degree of polymerization n is 500, 15 parts; Carboxyl-terminated nitrile rubber: acrylonitrile mass content is 20%, 7 parts.

[0055] A method for preparing a flexible printed circuit board for an automotive electronic control system comprises the following steps: Ⅰ. Raw material pretreatment: Drying the polyethylene naphthalate: Spread the polyethylene naphthalate obtained in Example 1 on a tray of a vacuum oven to ensure uniform thickness at 2 cm, start the vacuum oven, evacuate to a pressure of 0.01 MPa, raise the temperature to 135° C., and dry for 5 h; Weigh 8 parts by mass of silicon dioxide, disperse it in 100 parts by mass of anhydrous ethanol, add 0.16 parts by mass of γ-aminopropyltriethoxysilane, place the mixed solution in a three-necked flask with a condensation reflux device, put it into a constant temperature water bath, heat it to 70°C, turn on the magnetic stirring, control the speed at 300rpm, react for 3h, after the reaction is completed, filter it with a Buchner funnel, wash it with anhydrous ethanol 3 times, each time with 50 parts by mass, and then place the filter cake in a vacuum oven and dry it at 80°C and 0.01MPa for 3h; weigh 6 parts by mass of aluminum oxide, disperse it in 80 parts by mass of anhydrous ethanol, add 0.3 parts by mass of γ-aminopropyltriethoxysilane, stir and react at 75°C and 350rpm of magnetic stirring speed for 2.5h, and the filtering, washing and drying conditions are the same as those for silicon dioxide treatment; Ⅱ. Mixing: Start the twin-screw extruder, preheat to 290℃, set the screw speed to 250rpm, add the pretreated polyethylene naphthalate first, wait for it to melt in the screw and mix evenly, then start adding the compound raw materials in sequence; The order of addition is as follows: first add the surface-modified silica, keep the screw speed at 250rpm for 2min; then add the surface-modified alumina, stir for 2min at the same screw speed; then add the hyperbranched macromolecular flame-retardant carbonizing agent and ammonium polyphosphate, increase the screw speed to 300rpm, stir for 3min; then add the carboxyl-terminated nitrile rubber, keep the screw speed at 300rpm, stir for 2min; III. Molding Processing - Melt Extrusion Process: The mixed materials are conveyed to the extruder hopper through a screw conveyor. The extruder is divided into 5 heating zones from the hopper end to the head end. The temperature settings of each zone are: 295℃, 300℃, 305℃, 305℃, 310℃; the extrusion pressure is 30MPa; IV. Post-processing: Heat setting treatment: First heat setting: the extruded substrate is passed through a heat setting device with a fixed width. The internal temperature of the device is set to 220°C, the substrate transmission speed is 10cm / s, and the processing time is 15s, so that the substrate initially stabilizes its size and improves its mechanical properties; Second heat setting: the substrate is placed in a hot environment with a temperature of 210°C, and a relaxed suspension method is used to ensure the free shrinkage of the substrate. The processing time is 10s; nitrogen is introduced into the heat setting device for protection, and the nitrogen flow rate is controlled at 20L / min; Surface modification-plasma treatment: The formed substrate is placed in a vacuum chamber of a plasma treatment device, evacuated to a pressure of ≤0.005 MPa, oxygen plasma is selected, the gas flow rate is controlled at 30 mL / min, the plasma is excited by a radio frequency power supply, the processing power is 200 W, and the processing time is 60 s, thereby obtaining a flexible printed circuit board for an automotive electronic control system.

[0056] Application Example 3 In the process of preparing flexible printed circuit boards for automotive electronic control systems, the selection and mass fraction of each raw material are as follows: Polyethylene naphthalate obtained in Example 2: 100 parts; Silicon dioxide: fumed silicon dioxide with a particle size of 15 μm, 8 parts; Alumina: γ-alumina with an average particle size of 5 μm, 6 parts; Hyperbranched macromolecular flame retardant carbon-forming agent: weight average molecular weight is 15000, 10 parts; Ammonium polyphosphate: degree of polymerization n is 800, 15 parts; Carboxyl-terminated nitrile rubber: acrylonitrile content is 30%, 7 parts; Carbon nanotubes: multi-walled carbon nanotubes with a diameter of 20 nm and a length of 20 μm, 1.5 parts.

[0057] A method for preparing a flexible printed circuit board for an automotive electronic control system comprises the following steps: Ⅰ. Raw material pretreatment: Drying the polyethylene naphthalate: Spread the polyethylene naphthalate obtained in Example 2 on a tray of a vacuum oven to ensure uniform thickness at 3 cm, start the vacuum oven, evacuate to a pressure of 0.01 MPa, raise the temperature to 135° C., and dry for 5 h; Weigh 8 parts by mass of silicon dioxide, disperse it in 100 parts by mass of anhydrous ethanol, add 0.16 parts by mass of γ-aminopropyltriethoxysilane, place the mixed solution in a three-necked flask with a condensation reflux device, put it into a constant temperature water bath, heat it to 70°C, turn on the magnetic stirring, control the speed at 300rpm, react for 3h, after the reaction is completed, filter it with a Buchner funnel, wash it with anhydrous ethanol 3 times, each time with 50 parts by mass, and then place the filter cake in a vacuum oven and dry it at 80°C and 0.01MPa for 3h; weigh 6 parts by mass of aluminum oxide, disperse it in 80 parts by mass of anhydrous ethanol, add 0.3 parts by mass of γ-aminopropyltriethoxysilane, stir and react at 75°C and 350rpm of magnetic stirring speed for 2.5h, and the filtering, washing and drying conditions are the same as those for silicon dioxide treatment; Ⅱ. Mixing: Start the twin-screw extruder, preheat to 290℃, set the screw speed to 250rpm, add the pretreated polyethylene naphthalate first, wait for it to melt in the screw and mix evenly, then start adding the compound raw materials in sequence; The order of addition is as follows: first add the surface-modified silica, keep the screw speed at 250rpm for 2min; then add the surface-modified alumina, stir for 2min at the same screw speed; then add the hyperbranched macromolecular flame-retardant carbonizing agent and ammonium polyphosphate, increase the screw speed to 300rpm, stir for 3min; then add the carboxyl-terminated nitrile rubber, keep the screw speed at 300rpm, stir for 2min; add the carbon nanotubes, adjust the screw speed to 350rpm, stir for 3min, and the total time of the whole mixing process is controlled within 20min; III. Molding process - melt extrusion process: The mixed materials are conveyed to the extruder hopper through a screw conveyor. The extruder is divided into 5 heating zones from the hopper end to the head end. The temperature settings of each zone are: 295℃, 300℃, 305℃, 305℃, 310℃; the extrusion pressure is 20MPa; IV. Post-processing: Heat setting treatment: First heat setting: the extruded substrate is passed through a heat setting device with a fixed width. The internal temperature of the device is set to 220°C, the substrate transmission speed is 10cm / s, and the treatment time is 15s, so that the substrate initially stabilizes its size and improves its mechanical properties; Second heat setting: the substrate is placed in a hot environment with a temperature of 210°C, and a relaxed suspension method is used to ensure the free shrinkage of the substrate. The treatment time is 10s; nitrogen is introduced into the heat setting device for protection, and the nitrogen flow rate is controlled at 10L / min; Surface modification-plasma treatment: The formed substrate is placed in a vacuum chamber of a plasma treatment device, evacuated to a pressure of ≤0.005 MPa, oxygen plasma is selected, the gas flow rate is controlled at 30 mL / min, the plasma is excited by a radio frequency power supply, the processing power is 200 W, and the processing time is 60 s, thereby obtaining a flexible printed circuit board for an automotive electronic control system.

[0058] Application Comparative Example 1 Compared with Application Example 1, the difference is that silicon dioxide and hyperbranched macromolecular flame retardant carbon-forming agent are not added.

[0059] Application Comparative Example 2 Compared with Application Example 1, the difference is that ammonium polyphosphate and carboxyl-terminated nitrile rubber are not added.

[0060] The test data of application examples 1-3 and application comparative examples 1-2 are shown in Table 2.

[0061] Table 2: Test data of application examples 1-3 and application comparative examples 1-2

[0062] Test method for dimensional stability: Initial dimension measurement: At room temperature (25°C), use calibrated measuring tools to accurately measure the initial dimensions of each sample in different directions (such as length represented by L0 and width represented by W0), and keep records.

[0063] Low temperature test: Place the sample steadily in a high and low temperature test chamber, lower the temperature to -40°C at a cooling rate of 5°C / min, and maintain it at this temperature for 2 hours to allow the sample to fully reach thermal equilibrium. After that, use a measuring tool to measure the dimensions of the sample in all directions again, and record the measured value in the length direction as L1 and the width direction as W1.

[0064] High temperature test: starting from -40℃, raise the temperature to 120℃ at a heating rate of 5℃ / min, and keep it at this temperature for 2h. After the sample reaches thermal equilibrium, measure and record the dimensions of the sample in each direction at this time. The length direction is recorded as L2, and the width direction is recorded as W2.

[0065] Calculation of dimensional change rate: Based on the measured data, calculate the dimensional change rate in the length and width directions respectively. The calculation formula is as follows: Dimension change rate in length direction at low temperature: ΔL%=(L1-L0) / L0×100% Dimension change rate in length direction at high temperature: ΔL%=(L2-L0) / L0×100% Dimension change rate in width direction at low temperature: ΔW%=(W1-W0) / W0×100% Dimension change rate in width direction under high temperature: ΔW%=(W2-W0) / W0×100%.

[0066] From the test data in Table 2, it can be seen that the flexible printed circuit board for automotive electronic control systems produced by polyethylene naphthalate has better overall performance and can meet industrial needs, especially for flexible printed circuit boards used in automotive engine control units, in-vehicle entertainment systems, and airbag control systems.

Claims

1. A method for preparing polyethylene naphthalate, characterized in that: The following steps are involved: (1) Adding 100 parts of 2,6-naphthalene dicarboxylic acid dimethyl ester containing a modified component, 60-75 parts of ethylene glycol, 10-30 parts of terephthalic acid, 5-20 parts of pyromellitic anhydride, 5-20 parts of 1,4,5,8-naphthalene tetracarboxylic anhydride, 5-15 parts of cardanol, 0.05-1 parts of an organic nucleating agent, 1-5 parts of a composite heat stabilizer, 8-20 parts of a halogen flame retardant, 0.1-1 parts of an antioxidant, 0.5-3 parts of an antistatic agent and a composite catalyst solution into a reactor for ester exchange reaction, wherein the amount of the composite catalyst solution is determined by 0.05%-0.5% of the mass of 2,6-naphthalene dicarboxylic acid dimethyl ester containing a modified component; heating and heating, the stirring speed is controlled at 50-200 rpm, the reaction temperature is controlled at 180-220°C, and the reaction time is 2-6 hours; (2) After the transesterification reaction is completed, the temperature is raised to 260-280°C, and the pressure of the reaction system is reduced to 10-100 Pa to carry out polycondensation reaction for 1-3 hours; (3) After the polycondensation reaction is completed, the heating is stopped and the mixture is cooled naturally under the protection of nitrogen. When the temperature drops to 100-150°C, the product is discharged from the reactor and pelletized to obtain granular polyethylene naphthalate; The preparation method of dimethyl 2,6-naphthalene dicarboxylate containing a modified component comprises the following steps: a. Add the nano-silica suspension to the reactor, then add 100 parts by mass of naphthalene, 200 parts by mass of methanol, 5 parts by mass of pyromellitic anhydride, 10 parts by mass of dimethyl adipate and 0.5 parts by mass of ammonium perfluorooctane sulfonate to the reactor, start stirring, control the speed at 300-500rpm, dissolve 3 parts by mass of trimethyl phosphate in 10-15 parts by mass of methanol, and then add the reactor, then close the reactor, introduce nitrogen to replace the air in the reactor 3-5 times, and then introduce carbon monoxide to raise the pressure in the reactor to 3.5-5MPa; b. Turn on the heating device, raise the temperature to 190-220°C, and maintain the reaction for 6-10 hours. During this period, continue stirring to ensure uniform reaction. At the same time, continuously add carbon monoxide through the pressure control system to maintain stable reaction pressure; c. After the reaction is completed, stop heating, close the carbon monoxide inlet valve, cool the reactor naturally to 80-100°C, open the reactor, and filter the reaction liquid through a filter; d. The filtered solution was transferred to a distillation apparatus and distilled under vacuum conditions of 5-10 KPa, and the fraction at 150-200 ° C was collected, which was dimethyl 2,6-naphthalene dicarboxylate containing the modified component; The organic nucleating agent is di(3,4-dimethylbenzylidene) sorbitol, the composite heat stabilizer is prepared by antioxidant 1010 and tri(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:(1.5-2), the antioxidant is antioxidant 168, and the antistatic agent is stearyl trimethyl ammonium chloride; The method for preparing the composite catalyst solution comprises the following steps: ① Preparation of zinc acetate solution and tetraisopropyl titanate solution: Weigh 10 parts by mass of zinc acetate and 15 parts by mass of tetraisopropyl titanate, and place them in two clean and dry stoppered glass bottles A and B respectively; add 75 parts by mass of toluene to bottle A containing zinc acetate, place bottle A on a magnetic stirrer, adjust the speed to 400 rpm, and stir for 12 minutes; add 75 parts by mass of toluene to bottle B containing tetraisopropyl titanate, also place it on a magnetic stirrer, and stir at 400 rpm for 12 minutes to completely dissolve the tetraisopropyl titanate; ② Preparation of dibutyltin dilaurate solution: weigh 8 parts by mass of dibutyltin dilaurate and put it into a clean stoppered glass bottle C; add 120 parts by mass of acetone, place the glass bottle C on a magnetic stirrer, adjust the speed of the magnetic stirrer to 500 rpm, and stir for 18 minutes; ③ Preparation of antimony trioxide dispersion: Weigh 10 parts by mass of antimony trioxide and 0.6 parts by mass of sodium dodecylbenzene sulfonate, and put them into a stoppered glass bottle D containing 180 parts by mass of deionized water; put the glass bottle D into an ultrasonic cleaner, adjust the ultrasonic power to 300 W, and the ultrasonic time to 25 min; ④ Composite catalyst mixing: Mix the zinc acetate solution and tetraisopropyl titanate solution in bottles A and B in a clean three-necked flask, place on a magnetic stirrer, and stir at a speed of 300 rpm for 8 minutes; use a dropping funnel to drop the dibutyltin dilaurate solution in bottle C into the three-necked flask at a rate of 1.5 drops / s, and continue stirring during the dropping process. After the dropping is completed, keep the stirring speed at 300 rpm and continue stirring for 12 minutes. Add the antimony trioxide dispersion in bottle D to the three-necked flask at a rate of 0.8 drops / s, and add 1.54 parts by mass of polyvinyl pyrrolidone as a high molecular polymer dispersant; after the addition is completed, keep the stirring speed at 300 rpm and stir for 25 minutes to obtain a preliminary composite catalyst solution; ⑤ Add 0.66 parts by mass of disodium ethylenediaminetetraacetate to the preliminary composite catalyst solution, and stir on a magnetic stirrer at a speed of 300 rpm for 7 minutes to obtain a composite catalyst solution.

2. The method for preparing polyethylene naphthalate according to claim 1, characterized in that: The naphthalene in the step a needs to be dried in a vacuum oven at 80-100° C. for 4-6 hours before being added; the amount of nano-silicon dioxide added is 2 parts by mass.

3. The method for preparing polyethylene naphthalate according to claim 1, characterized in that: The cardanol is 3-pentadecylphenol, and the halogen flame retardant is decabromodiphenylethane.

4. A polyethylene naphthalate, characterized in that: The polyethylene naphthalate is prepared by the preparation method of any one of claims 1 to 3.

5. An application of the polyethylene naphthalate according to claim 4, characterized in that: Used for the preparation of flexible printed circuit boards for automotive electronic control systems.

6. The use of polyethylene naphthalate according to claim 5, characterized in that: The method for preparing the flexible printed circuit board of the automotive electronic control system comprises the following steps: Ⅰ. Raw material pretreatment: Drying of polyethylene naphthalate: Spread polyethylene naphthalate on a tray of a vacuum oven to ensure uniform thickness of 2-3 cm, start the vacuum oven, evacuate to a pressure of ≤0.01 MPa, heat to 135°C, and dry for 5 hours; Weigh 8 parts by mass of silicon dioxide, disperse it in 100 parts by mass of anhydrous ethanol, add 0.16 parts by mass of γ-aminopropyltriethoxysilane, place the mixed solution in a three-necked flask with a condensation reflux device, put it into a constant temperature water bath, heat it to 70°C, turn on the magnetic stirring, control the speed at 300rpm, react for 3h, after the reaction is completed, filter it with a Buchner funnel, wash it with anhydrous ethanol 3 times, each time with 50 parts by mass, and then place the filter cake in a vacuum oven, dry it at 80°C and pressure ≤0.01MPa for 3h; weigh 6 parts by mass of aluminum oxide, disperse it in 80 parts by mass of anhydrous ethanol, add 0.3 parts by mass of γ-aminopropyltriethoxysilane, stir and react at 75°C and a magnetic stirring speed of 350rpm for 2.5h, and the filtering, washing and drying conditions are the same as those for silicon dioxide treatment; Ⅱ. Mixing: Start the twin-screw extruder, preheat to 290℃, set the screw speed to 250rpm, add the pretreated polyethylene naphthalate first, wait for it to melt in the screw and mix evenly, then start adding the compound raw materials in sequence; The order of addition is: first add the surface-modified silica, keep the screw speed at 250rpm for 2min; then add the surface-modified alumina, stir for 2min at the same screw speed; then add the hyperbranched macromolecular flame-retardant carbon-forming agent and ammonium polyphosphate, increase the screw speed to 300rpm, stir for 3min; then add the carboxyl-terminated nitrile rubber, keep the screw speed at 300rpm, stir for 2min; the hyperbranched macromolecular flame-retardant carbon-forming agent is Realgard™ 9898; III. Molding Processing - Melt Extrusion Process: The mixed materials are conveyed to the extruder hopper through a screw conveyor. The extruder is divided into 5 heating zones from the hopper end to the head end. The temperature settings of each zone are: 295℃, 300℃, 305℃, 305℃, 310℃; IV. Post-processing: Heat setting treatment: primary heat setting: the extruded substrate is passed through a heat setting device with a fixed width, the internal temperature of the device is set to 220°C, the substrate transmission speed is 10cm / s, and the treatment time is 15s, so that the substrate can initially stabilize its size and improve its mechanical properties; secondary heat setting: the substrate is placed in a hot environment with a temperature of 210°C, and a relaxed suspension method is used to ensure the free shrinkage of the substrate. The treatment time is 10s; Surface modification-plasma treatment: The formed substrate is placed in a vacuum chamber of a plasma treatment device, evacuated to a pressure of ≤0.005 MPa, oxygen plasma is selected, the gas flow rate is controlled at 30 mL / min, the plasma is excited by a radio frequency power supply, the processing power is 200 W, and the processing time is 60 s, thereby obtaining a flexible printed circuit board for an automotive electronic control system.

7. The use of polyethylene naphthalate according to claim 6, characterized in that: In the process of preparing the flexible printed circuit board for the automotive electronic control system, the selection and mass fraction of each raw material are as follows: Polyethylene naphthalate: 100 parts; Silicon dioxide: fumed silicon dioxide with a particle size of 5-15 μm, 8 parts; Alumina: γ-alumina with an average particle size of 3-5 μm, 6 parts; Hyperbranched macromolecular flame retardant carbon-forming agent: weight average molecular weight is 10000-15000, 10 parts; Ammonium polyphosphate: degree of polymerization n is between 500-800, 15 parts; Carboxyl-terminated nitrile rubber: acrylonitrile mass content is 20-30%, 7 parts.

Citation Information

Patent Citations

  • Synthesis method of 2, 6-naphthalic acid

    CN117945881A

  • Refining device of dimethyl 2, 6-naphthalate

    CN217661568U

  • Production of 2,3,6-naphthalenetricarboxylic acid

    JP1989090153A